2018
DOI: 10.1186/s13018-017-0693-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bone marrow aspirate concentrate and platelet-rich plasma on patients with partial tear of the rotator cuff tendon

Abstract: BackgroundWe compared the clinical course of rotator cuff tears between rotator cuff exercise and bone marrow aspirate concentration (BMAC)-platelet rich plasma (PRP) injection to identify the therapeutic effects of BMAC-PRP on partial tear of the rotator cuff tendon.MethodsTwenty-four patients with partial tear of the rotator cuff tendon participated in this study. Twelve patients underwent extraction of BMACs and PRP and received the injection of BMAC-PRP at the tear site under ultrasound guidance. Twelve pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 45 publications
6
115
1
Order By: Relevance
“…Exercise therapy patients completed the stretching, strengthening, and stability exercises at home, with the opportunity to cross over to the treatment group after at least 3 months of the home exercise program if desired improvement was lacking. The duration of three months of exercise therapy is in line with other published research using exercise therapy for torn rotator cuffs [4,21,32,33]. Patients were followed for 24 months after receiving BMC treatment.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…Exercise therapy patients completed the stretching, strengthening, and stability exercises at home, with the opportunity to cross over to the treatment group after at least 3 months of the home exercise program if desired improvement was lacking. The duration of three months of exercise therapy is in line with other published research using exercise therapy for torn rotator cuffs [4,21,32,33]. Patients were followed for 24 months after receiving BMC treatment.…”
Section: Methodsmentioning
confidence: 76%
“…As an alternative treatment, early research on regenerative therapies such as platelet-rich plasma (PRP) and bone marrow concentrate (BMC) has shown promise in enhancing the healing properties of torn rotator cuff tendons, reducing retear rates over time, and improving symptoms and function [20][21][22]. BMC contains mesenchymal stem cells (MSCs) which are multipotent, readily available, and immune-privileged that contribute to tissue healing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BMMSCs support the recruitment of cells to neoangiogenic treatment sites to accelerate local revascularization [ 10 ]. Kim et al demonstrated that in the absence of an adequate scaffold, the survival rate of BMMSCs and their reparative and differentiation capacity to enhance healing are jeopardized [ 178 ]. Although tissue harvesting, specimen preparation, and mechanism of action are different for PRP and BMACs, studies have shown that they can complement each other [ 179 , 180 ].…”
Section: The Role Of Platelets In Bone Marrow Aspirate Concentratmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) is a whole-blood fraction containing high platelet concentrations, which can release various growth factors mentioned above to promote healing [ 7 ]. Studies have reported that PRP can be used in the management of tendinopathy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%